2022
DOI: 10.1088/2399-6528/ac678f
|View full text |Cite
|
Sign up to set email alerts
|

Resonance modes of a metal-semiconductor-metal multilayer mediated by electric charge

Abstract: Electromagnetic fields around metal–semiconductor–metal (MSM) multilayers with square island top layers were numerically simulated to elucidate the difference in physics between the circuit resonance and Fabry–Pérot interference mediated by the surface plasmon polaritons (SPP). In the current study, the top and bottom metal layers were made of gold, and the intermediate semiconductor layer was a gallium antimony (GaSb). The lumped-element and Fabry–Pérot interference models showed less accuracy when the island… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…A finite length of the waveguide gives a strict coupling requirement between the incident wave and SRSPs because the terminus of waveguide functioning as an end-fire coupler slightly reflects the SRSPs (Bozhevolnyi and Søndergaard, 2007). The incident and reflected SRSPs exhibit Fabry-Pérot-like interference using the MIM waveguide as a resonator (Barnard et al, 2008;Bozhevolnyi, 2009;Bozhevolnyi and Søndergaard, 2007;Isobe and Hanamura, 2022;Liu and Takahara, 2017). SRSPs are excited in the finite waveguide when the grating height corresponds to the integer multiples of the half wavelength; however, the actual resonance point is corrected by the phase shift at the terminus of the waveguide.…”
Section: Tanh(𝛾mentioning
confidence: 99%
See 1 more Smart Citation
“…A finite length of the waveguide gives a strict coupling requirement between the incident wave and SRSPs because the terminus of waveguide functioning as an end-fire coupler slightly reflects the SRSPs (Bozhevolnyi and Søndergaard, 2007). The incident and reflected SRSPs exhibit Fabry-Pérot-like interference using the MIM waveguide as a resonator (Barnard et al, 2008;Bozhevolnyi, 2009;Bozhevolnyi and Søndergaard, 2007;Isobe and Hanamura, 2022;Liu and Takahara, 2017). SRSPs are excited in the finite waveguide when the grating height corresponds to the integer multiples of the half wavelength; however, the actual resonance point is corrected by the phase shift at the terminus of the waveguide.…”
Section: Tanh(𝛾mentioning
confidence: 99%
“…An earlier research study investigated the resonance frequencies and electromagnetic fields for SPPs excited as a short-range surface plasmon (SRSP) mode inside an MIM waveguide. The study showed that the Fabry-Pérot-like interference for SRSPs in a MIM multilayer with a square island top layer denotes similar resonance frequency as circuit resonance (Isobe and Hanamura, 2022). However, the results contained slight deviations of models from simulation results because two metal layers sandwiching the insulator layer had different shapes; one metal layer was a smooth plane while another was a square island structure.…”
Section: Introductionmentioning
confidence: 95%